Nayab zumard - Zubaida sultana (Ferozsons (Pvt) Limited ; Lahore, 2000)
"Nayab Zumard" is an inspiring story of courage and resilience, centered around a unique and exceptional individual whose extraordinary qualities challenge societal norms and lead to a transformative journey of self-discovery and empowerment.